Fructokinases (FRKs) of potato (Solanum tuberosum L.): Sequence analyses of FRK cDNAs, and studying amplicon profiles in the cultivars using FRK-specific oligonucleotide primers - Kaur, Harleen (My University, 2015)
Hexose kinases are the enzymes which catalyze the phosphorylation of hexose sugars. Fructokinase (FRK) belongs to this enzyme family; it phosphorylate fructose (substrate) to fructose-6-phosphate which then further acts as one of the precursor for starch biosynthesis in plants. FRK is dimeric in nature, and molecular weight is in the range of 75-100 kDa with high specificity only towards fructose (Km value 0.02-0.1 mM). Different isoforms of FRKs have been identified and their cDNA studies have been done in different plants like tomato, peas, barley and potato. Review of literature revealed that in the Solanaceae family, no considerable progress has been made on gene structure and function of FRK till date. The expression patterns of FRK gene(s) during different stages of tuberization are yet to be explored. With regard to the Indian potato cultivars there is no report on FRK is available. In the first instance, the available FRK cDNAs were used for sequence comparison at both nucleotide and amino acid levels. Based on sequence comparison, some salient sequence features were presented in this report including hydropathy characters of FRK. Isolation of good quality genomic DNA was carried out from different potato cultivars, and the quality and quantity were checked by spectrophotometric analyses. A number of oligonucleotide primers were made based on the available FRK cDNA sequences in the database. Polymerase chain reactions (PCR) were carried out using specific primer pairs and different potato genomic DNAs template. Amplicon profiles were noted and analyzed for each PCR. Apart from the expected ones, some cultivar-specific amplicons as found in the study need to be studied in detail at molecular level. This report would be quite useful with regard to understanding structure and function of FRK genes in the Solanaceae family, particularly in potato.
M.Tech-Biotechnology
Keywords: Hexose kinases; Fructokinases; cDNAs; Potato; Sequence analyses; Genomic DNA; PCR; BTES; biotechnology